General Idi Amin Dada - A Self Portrait - Schroeder, Barbet (The Criterion Collection, 2002)
Of all the dictators of the 20th century, few were as nefarious as General Idi Amin Dada. After seizing power in a 1971 coup, he ruled Uganda with an iron fist and an erratic temper. He forcibly expelled the country's entire Asian population in 1972. He executed an estimated 200,000 people for the most trivial of offenses. Throughout his eight-year reign, he alternately shocked and baffled the world by sending strange, rambling telegrams to heads of state, making bizarre demands of foreign governments, and actively supporting terrorism. [www.reel.com]